Nanox: a miniature mechanical stress rig designed for near‐field X‐ray diffraction imaging techniques. (18th October 2016) - Gueninchault, N.; Proudhon, H.; Ludwig, W.
Abstract : A compact design for a miniature tensile stress rig, compatible with the space and weight constraints imposed by near‐field diffraction imaging techniques, is presented. The device can carry tensile loads up to 500 N and is driven by a piezoelectric actuator which can work in a static and dynamic regime up to frequencies of 100 Hz. Abstract : Multi‐modal characterization of polycrystalline materials by combined use of three‐dimensional (3D) X‐ray diffraction and imaging techniques may be considered as the 3D equivalent of surface studies in the electron microscope combining diffraction and other imaging modalities. Since acquisition times at synchrotron sources are nowadays compatible with four‐dimensional (time lapse) studies, suitable mechanical testing devices are needed which enable switching between these different imaging modalities over the course of a mechanical test. Here a specifically designed tensile device, fulfilling severe space constraints and permitting to switch between X‐ray (holo)tomography, diffraction contrast tomography and topotomography, is presented. As a proof of concept the 3D characterization of an Al–Li alloy multicrystal by means of diffraction contrast tomography is presented, followed by repeated topotomography characterization of one selected grain at increasing levels of deformation. Signatures of slip bands and sudden lattice rotations inside the grain have been shown by means of in situ topography carried out during the load ramps, and diffraction spot peak broadening has been monitored throughout the experiment.